Working Without Commitments: The Health Effects of Precarious Employment - Lewchuk, Wayne; Clarke, Marlea; De Wolff, Alice (McGill-Queen's University Press, 2011)
From the end of the Second World War to the early 1980s, the North American norm was that men had full-time jobs, earned a "family wage," and expected to stay with the same employer for life. In households with children, most women were unpaid caregivers. This situation began to change in the mid-1970s as two-earner households became commonplace, with women entering employment through temporary and part-time jobs. Since the 1980s, less permanent precarious employment has increasingly become the norm for all workers. Working Without Commitments offers a new understanding of the social and health impacts of this change in the modern workplace, where outsourcing, limited term contracts, and the elimination of pensions and health benefits have become the new standard. Using information from interviews and surveys with workers in less permanent employment, the authors show how precarious employment affects the health of workers, labour productivity, and the sustainability of the traditional family model. --Publisher's description. Contents: Working without commitments: employment relationships and health -- A short history of the employment relationship: control, effort, and support -- Working without commitments and the characteristics of the employment relationship -- Gender, race, and the characteristics of the employment relationship -- The employment strain model and the health effects of less permanent employment -- The blurred lines between precariousness and permanence -- Sustainable, less permanent employment -- "On a path" to employment security? -- Unsustainable, less permanent employment -- Creating commitments in less permanent employment: policy reforms to address rising insecurity.
Keywords: Health aspects; Job stress; Precarious Employment; Social aspects